Studies relative to the β-disintegration of some heavy elements, using a magnetic spectrometer of high collecting power - Fairweather, Ian L. (The University of Edinburgh, 1958)
In recent years the improved methods of nuclear spectroscopy have provided an increasing body of information about the modes of disintegration of both naturally occurring and artificially produced radio-elements. This has led to the development of nuclear models which are capable of interpreting the nuclear data in terms of the properties of the nuclear structure with some success. Spins and parities are assigned to nuclear energy levels, and selection rules have been formulated by which the observed decay properties can be explained fairly consistently. The properties of the nuclear levels can be established from a variety of measurements. In ß- and γ -ray spectroscopy these include the relative intensities and high energy end-points of the partial components of the ß-speetrum, determined by the method of Fermi analysis from the continuous spectrum produced in the (ß-decay of a parent nucleus, and the intensities, lifetimes and multipole nature of subsequent γ- transitions between higher and lower lying energy levels in the daughter nucleus. These γ-transitions give rise to internal conversion electrons which are superimposed as mono-energetic lines on the continuous ß-spectrum. The internal conversion electrons are formed through the interaction of a γ-ray of energy Eγ with an electron of the K, L, -shell of the product nucleus. The energy Eß of the electrons emitted from the shell is given by Eß = Eγ - Eₖ (or Eₗ ), where Eₖ' (or Eₗ', ) is the binding energy of the K, L, -shell electrons in the pro¬ duct atom. It is customary to speak of the conversion of the γ-rays although it is now recognised that the electron emission is a competitive decay process resulting from the mutual interaction of the overlapping nuclear and electronic wave functions. The relative conversion efficiencies for γ-rays in the different shells or sub-shells and the ratio of conversion electrons to photon de-excitations (the conversion coefficients) in an atom depend, along with their lifetimes, on the energy and multipole nature of the radiation. The absolute intensities of the conversion lines, together with theoretically or experimentally determined conversion coefficients, permit the total intensities of y-transitions to be calculated relative to the total number of ß-transitions. The energies and intensities of the ß- and γ-transitions in conjunction with γ-ray studies may then form the basis of a complete disintegration scheme, while measurements of the coincidence of ß- and γ-transitions may be made to decide conclusively between possible level schemes. The present investigations on the electron spectrum of heavy radio-elements were undertaken with a magnetic spectrometer and provide information on the energies and intensities of ß-transitions and internally converted γ-transitions. The spectrometer has recently been equipped with a γ-ray detector which, with the possibility of making ß-γ coincidence measurements, will extend its capabilities in future studies. The spectrometer was designed by Richardson (1, 2) and the performance has been investigated and described, by Braid and Richardson (3). A description of the spectrometer is given in Chapter 3 but those features that distinguish it from conventional ß-particle spectrometers will be mentioned here, together with those properties that determine the type of radio-element that can be most profitably investigated.